DIKSI DAN GAYA BAHASA DALAM CERAMAH AGAMA TENGKU HANAN ATTAKI - Alamsyah, Fajar; Suputra, I Gusti Ketut Alit; Harisah, Sitti (BAHASANTODEA, 2017)
The main problem in this research is how the use of diction and style of language in Tengku Hanan Attaki religious lecture? This study aims to describe the use of diction and style of language in religious lectures Tengku Hanan Attaki. The type of research used in this study is qualitative research and the method used in this research is descriptive method. Sources of data in this study comes from a video lecture Tengku Hanan Attaki religious residing in social media Youtube. Techniques used in data collection is a technique refer and note. Instruments in this study is a laptop to listen to religious lectures and stationery to record. Data analysis techniques in this study follow three stages, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions. In this study found the use of diction and style of language in religious lectures Tengku Hanan Attaki. The use of diction in the religious lecture of Tengku hanan Attaki is divided into two, namely the type of meaning and meaning relation. This type of meaning is divided into thirteen, meaning lexical, grammatical, contextual, referential, nonreferential, denotative, connotative, proverbial, colocative, thematic, common and special word, and progem language. The relation of meaning is divided into two, namely synonym and antonym. The use of language style in the Tengku Hanan Attaki religious lecture is divided into three, namely the style of language comparison, linkage, and repetition. Comparative language style is metaphorical and metaphorical, intermediate language style is antonomia, and the style of repetition language is epizeukis.